The Effects of Multi Vitamins Supplementation in the Prevention of Preeclampsia - Ranjit S. Ambad1 , Nandkishor Bankar2 , Lata Kanyal Butola3 , Minal Kalambe4 , Brij Raj Singh5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Preeclampsia is a multifactorial pregnancy-specific disorder which is symbolized by thedevelopment of hypertension and proteinuria after 20 weeks of gestation. With the greatest morbidity andmortality, preeclampsia affects 5% to 7% of all pregnant women.Material And Method: 390 subjects were included in the study and were grouped.Results: Mean maternal age of cases in years was observed as 26.68±4.2, mean gestational age in weeks was36.2. Systolic and diastolic BP in mmHg was 159.4 and 104.8 respectively. Mean weight was observed as72.6 Kg and Height was 158.4 cm. There was statically significant correlation observed between vitamins inGroup I and Group II, but Vitamin E and Vit B 12 does not show any significant correlation between them.No Stastical significance were found in the vitamins level in Group III and Group II. Statistically significantdifference was observed between group I and Group III, for vitamin B12, vitamin D, vitamin C and vitaminA. No statistical significance difference was observed in vitamin E levels.Conclusion: The intended intervention of Vitamins has a protective effect against recurrent preeclampsia.Vitamins supplementation therapy in pregnancy could help in reducing the incidence of gestationalhypertension/preeclampsia.